GAMBARAN PERILAKU PEMANFAATAN VCT (Voluntary Counseling and Testing) PADA LSL DI LSM SGC (Semarang Gaya Community) KOTA SEMARANG - Erdelia Herdanindita; Priyadi Nugraha Prabamurti; Bagoes Widjanarko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
HIV / AIDS is a sexually transmitted disease that attacks human immunity. MSM (men having sex with men) is one of the risk groups for HIV / AIDS transmission. Semarang City was ranked first as the highest number of HIV cases in Central Java Province in 2018 with 332 cases. A preliminary survey conducted at the SGC NGO on the results of STBP number of MSM who carried out VCT as many as 209 people in June 2014-February 2015. This study aims to describe the behavior of utilizing VCT on MSM in the SGC NGO Semarang City. This research uses a qualitative approach. 4 MSM informants at SGC NGOs with inclusion live in Semarang City, and were willing to become informants. Data collected by conducting in-depth interviews and observations. Analyzed descriptively and presented in narrative form. The results showed that almost all informants had good behaviour through VCT utilization. They are routinely using VCT services, have sufficient knowledge and perceptions related to HIV / AIDS and VCT, good availability of VCT service infrastructure, affordability of information facilities, support for the use of VCT by counselors, sexual partners, and community friends. However, access to night VCT services is still constrained by night service schedules 1-2 times a month at one health service. It can be concluded that knowledge, perception, availability of infrastructure, HIV / AIDS and VCT information facilities, as well as the support of counselors, sexual partners, and community friend influence the use of VCT. Meanwhile, attitudes related to HIV / AIDS as well as VCT and family support do not influence the use of VCT in MSM.